2018
DOI: 10.3390/molecules23071627
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Aroma Characteristics for Cubeb Berries by Sensomics Approach with Chemometrics

Abstract: The dried cubeb berries are widely used as medicinal herb and spicy condiment with special flavor. However, there is a significant definition discrepancy for cubeb berries. In this study, an efficient analytical method to characterize and discriminate two popular cubeb fruits (Litsea cubeba and Piper cubeba) was established. The aroma profiles of cubeb berries were evaluated by different extraction methods including hydro-distillation, simultaneous distillation/extraction, and solid-phase micro-extraction foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Also, the obtained results showed that the CEO is rich in eugenol compounds, which was reported as a source for omethyl eugenol (Herrmann and Weaver 1999). In the same line with the present findings, Cheng et al (2018) reported that components of the oil of berries of P. cubeba, that were extracted using hydro-distillation (HDE) and simultaneous distillation extraction (SDE) and identified by GC-MS were similar to the obtained finding, especially methyl eugenol with traces amount of 0.71 and 0.11% by HD and SDE, respectively. Also, terpinen-4-ol (42.41%), α-copaene (20.04%), and γ-elemene (17.68%) were the major components of P. cubeba EO (Andriana et al, 2019).…”
Section: -Ceo Volatile Componentssupporting
confidence: 92%
“…Also, the obtained results showed that the CEO is rich in eugenol compounds, which was reported as a source for omethyl eugenol (Herrmann and Weaver 1999). In the same line with the present findings, Cheng et al (2018) reported that components of the oil of berries of P. cubeba, that were extracted using hydro-distillation (HDE) and simultaneous distillation extraction (SDE) and identified by GC-MS were similar to the obtained finding, especially methyl eugenol with traces amount of 0.71 and 0.11% by HD and SDE, respectively. Also, terpinen-4-ol (42.41%), α-copaene (20.04%), and γ-elemene (17.68%) were the major components of P. cubeba EO (Andriana et al, 2019).…”
Section: -Ceo Volatile Componentssupporting
confidence: 92%
“…In FR1, the most abundant compound was methyl acetate, which has been identified in varieties of wild strawberry and gives a floral note to those fruits [ 26 ]. In the FR3–FR5 stages, the most abundant compound was most abundant was 1-butanol, 2-methyl-, acetate; this compound has an impact on the aroma of strawberry fruits in late stages of maturation and has been previously identified in other strawberry varieties such as Camarosa [ 27 ]. Finally, in stage FR6, hexanoic acid methyl ester was the VOC with the highest concentration, which indicates that this compound is closely related to the aroma of mature strawberries ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…SDE has been used for the isolation and quantification of Rio off-flavor compounds (e.g., 2-, 4-, and 6-trichloroanisole) from green coffee (Spadone, Takeoka, & Liardon, 1990), sulfur-containing aroma compounds (e.g., 3-methyl-2-butene-1-thiol, 3-mercapto-3-methylbutanol, and 3-mercapto-3-methylbutyl formate) from roasted coffee (Holscher, Vitzthum, & Steinhart, 1992), and linalool (3,7-dimethylocta-1,6-dien-3-ol) from green and roasted coffee (Bonnländer, Cappuccio, Liverani, & Winterhalter, 2006). SDE is a convenient and versatile extraction method (Chaintreau, 2001;Cheng, Chen, & Watkins, 2018;Riu-Aumatell, Vargas, & Vichi, 2011;Zhang & Li, 2010), but drawbacks include being timeconsuming due to multiple steps, a requirement for large amounts of solvent, and propensity for unstable compounds to be thermally decomposed and degraded at the time of the distillation process (Chaintreau, 2001;Zhang & Li, 2010). At the time of extraction due to high temperature, many heat-sensitive flavor compounds may breakdown or produce artificial compounds that do not normally exist in the sample (Chaintreau, 2001;Riu-Aumatell et al, 2011;Sheibani, Duncan, & Kuhn, 2016) unless careful optimization is carried out (Escudero & Etiévant, 1999;Sheibani et al, 2016).…”
Section: Simultaneous Distillation-extractionmentioning
confidence: 99%